Quality measures in HCC care by the Practice Metrics Committee of the American Association for the Study of Liver Diseases. Issue 5 (20th December 2021) - Asrani, Sumeet K.; Ghabril, Marwan S.; Kuo, Alexander; Merriman, Raphael B.; Morgan, Timothy; Parikh, Neehar D.; Ovchinsky, Nadia; Kanwal, Fasiha; Volk, Michael L.; Ho, Chanda; Serper, Marina; Mehta, Shivang; et al.
Abstract: The burden of HCC is substantial. To address gaps in HCC care, the American Association for the Study of Liver Diseases (AASLD) Practice Metrics Committee (PMC) aimed to develop a standard set of process‐based measures and patient‐reported outcomes (PROs) along the HCC care continuum. We identified candidate process and outcomes measures for HCC care based on structured literature review. A 13‐member panel with content expertise across the HCC care continuum evaluated candidate measures on importance and performance gap using a modified Delphi approach (two rounds of rating) to define the final set of measures. Candidate PROs based on a structured scoping review were ranked by 74 patients with HCC across 7 diverse institutions. Out of 135 measures, 29 measures made the final set. These covered surveillance (6 measures), diagnosis (6 measures), staging (2 measures), treatment (10 measures), and outcomes (5 measures). Examples included the use of ultrasound (± alpha‐fetoprotein [AFP]) every 6 months, need for surveillance in high‐risk populations, diagnostic testing for patients with a new AFP elevation, multidisciplinary liver tumor board (MLTB) review of Liver Imaging‐Reporting and Data System 4 lesions, standard evaluation at diagnosis, treatment recommendations based on Barcelona Clinic Liver Cancer staging, MLTB discussion of treatment options, appropriate referral for evaluation of liver transplantation candidacy, and role of palliative therapy. PROs include those related to pain, anxiety, fear of treatment, and uncertainty about the best individual treatment and the future. The AASLD PMC has developed a set of explicit quality measures in HCC care to help bridge the gap between guideline recommendations and measurable processes and outcomes. Measurement and subsequent implementation of these metrics could be a central step in the improvement of patient care and outcomes in this high‐risk population.